MEDIA MASSA, OLAH RAGA DAN POLITIK DALAM PENYELENGGARAAN PIALA DUNIA U-20 2023 (Analisa Wacana Kritis Pernyataan Penolakan Israel oleh Gubernur Jawa Tengah dan Gubernur Bali Pada Pemberitaan Media Daring Kompas.id Periode Maret 2023) - Nico Erdi Purwanto; Meistra Budiasa; Franky P Roring (Jurnal Communitarian (Prodi Ilmu Politik), 2023)
AbstractThe hosting of the 2023 FIFA U-20 World Cup in Indonesia was abruptly canceled by FIFA. FIFA revoked Indonesia's host status due to the growing discourse of rejecting the presence of the Israeli national team in Indonesia ahead of the event. The rejection was also supported by statements from the Governor of Central Java, Ganjar Pranowo, and the Governor of Bali, I Wayan Koster. According to both figures, the rejection of the Israeli national team is based on the mandate of Indonesia's constitution, which opposes all forms of colonialism, including Israel's occupation of Palestine. The discourse gained momentum as it was widely disseminated in the media. This research adopts Norman Fairclough's critical discourse analysis and employs qualitative research methods with a literature review of Kompas.id news during the period of March 2023. The research findings indicate that the hosting of the 2023 FIFA U-20 World Cup involves political elements within the discourse of rejecting the Israeli national team. There are three main findings: the constitution being cited as the reason for rejection, politics intervening in the domain of sports, and the media constructing the narrative in sports reporting. Kompas.id argues that these are two distinct domains that should not be mixed together.Keywords: Sports and politics, Critical Discourse Analysis, World Cup U-20, Rejection of Israel